2012
DOI: 10.1590/s1808-86942012000300019
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da expressão gênica de metaloproteinases de matriz e seus inibidores em colesteatomas por amplificação de ácidos nucleicos

Abstract: Acqui red middle ear cholesteatoma is a benign keratinizing hyperproliferative squamous epithelial lesion that may result in the destruction of the bone structures surrounding the temporal bone. Recent studies show that variations in cellular production of matrix metalloproteinases (MMPs) and their specific inhibitors (TIMPs) contribute to the pathophysiology of cholesteatoma. Objective:This study aims to analyze the use of RNA amplification tests to evaluate the expression of MMP and TIMP isoforms in choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, the numbers of MMP-2-positive cells increased in both groups of patients compared with the control group. These results are in an agreement with Banerjee et al [ 66 ], who showed no up-regulation of MMP-2 and MMP-9 compared with deep meatal skin, and with Rezende et al [ 67 ], whose study demonstrated that MMP-9 detected with the PCR method was negative in cholesteatoma samples. In addition, our study revealed that many samples of cholesteatoma were also negative or weakly stained for MMP-9 immunohistochemically.…”
Section: Discussionsupporting
confidence: 92%
“…However, the numbers of MMP-2-positive cells increased in both groups of patients compared with the control group. These results are in an agreement with Banerjee et al [ 66 ], who showed no up-regulation of MMP-2 and MMP-9 compared with deep meatal skin, and with Rezende et al [ 67 ], whose study demonstrated that MMP-9 detected with the PCR method was negative in cholesteatoma samples. In addition, our study revealed that many samples of cholesteatoma were also negative or weakly stained for MMP-9 immunohistochemically.…”
Section: Discussionsupporting
confidence: 92%
“…[ 9 ] Its substrates include collagen I, II, I to II, fibronectin, CD44, and so on. It can also activate other members of the MMP family, [ 10 ] induce angiogenesis, [ 5 ] and enhance cell metastasis. [ 11 ] At present, it is speculated that MMP-14 leads to bone invasion of cholesteatoma through the following ways: Activation of MMP-2: MMP-2 is type IV collagenase, which can degrade laminin and fibronectin of basement membrane.…”
Section: Discussionmentioning
confidence: 99%